Designing better spaces for people: Virtual reality and biometric sensing as tools to evaluate space use - Dias, J.; Eloy, S.; Carreiro, M.; Proença, P.; Moural, A.; Costa, T.; Freitas, J.; d'Alpuim, J.; Vilar, E. (Proceedings of the 19th International Conference on ComputerAided Architectural Design Research in Asia CAADRIA 2014, 2014)
We present a pilot study aiming to explore the use of biometrics sensing technology within a semi-immersive VR environment, where users face architectural spaces which induce them sensations close to fear of heights, claustrophobia, frustration and relief. Electrodermal activity was used to detect users’ emotional arousal, while navigating in VR. Navigation conditions and participants’ expertise with games were controlled. Main results show that physiological measurement of user’s perceptions can discriminate well "positive" from "negative" spaces, providing designers with basic information on people’s emotional state when using the buildings they design.